Upaya Meningkatkan Kemampuan Berhitung Permulaan Menggunakan Bahan Alam - Fitri Simanjuntak; Hasnah Siahaan (Atfaluna: Journal of Islamic Early Childhood Education, 2018)
This research aims to improve the starting ability of using natural materials. In the child group B in the PAUD Terpadu Rajawali, Kabupaten Samosir. This research is a study using the Kemmis Model and the Mc Tagart that is done in two cycles, of each cycle consists of 5 meetings. The study subject consisted of 20 children, 10 boys and 10 girls. This research object in the form of development improves the starting ability to use natural materials. Data collection uses observation and documentation. The results of this study indicate that the calculation of the start using natural materials and materials is around us.